Implant-Supported Prostheses Esthetic Outcomes After Socket Preservation Technique. Issue 3 (May 2015) - Perelli, Michele; Abundo, Roberto; Corrente, Giuseppe; Saccone, Carlo; Zambelli, Marta
<x xml:space="preserve">Abstract</x> Abstract Bone and soft tissue remodeling after tooth extraction may have dramatic effects. The socket preservation technique has demonstrated to be effective in maintaining volume before implant placement. The Pink Esthetic Score (PES) is an easy and complete evaluation of esthetic parameters. The aim of this study was to compare the PES index of anterior teeth needing to be replaced and the correspondent implant-supported prostheses after the socket preservation technique with 1 year of follow-up. Twenty-four patients were enrolled in this study. Eighteen maxillary central incisors and 6 maxillary lateral incisors were extracted, and then, every alveolar site was treated with the socket preservation technique and filled with Bio-Oss, mixed with fibrin glue, and covered with a collagen sponge. After 6 months of undisturbed healing, implants were placed and left healing for 4 months. After they were regularly loaded and at 1 year of follow-up, peri-implant PESs were recorded. All implants integrated successfully. No dropouts were recorded. Comparing PES results before extraction (mean, 12.25) and after implant loading (mean, 12.35), those around implants are similar if not better, and there are no statistically significant differences as analyzed with the t-test. The socket preservation technique combined with delayed implant placement and a standard healing time before implant loading has demonstrated to be effective in maintaining volumes and also esthetic values around implants compared with PES values before tooth extraction.